Respuesta :

Answer:

(- 3, - 5 )

Step-by-step explanation:

y = 4x + 7 → (1)

y = 8x + 19 → (2)

substitute y = 8x + 19 into (1)

8x + 19 = 4x + 7 ( subtract 4x from both sides )

4x + 19 = 7 ( subtract 19 from both sides )

4x = - 12 ( divide both sides by 4 )

x = - 3

substitute x = - 3 into either of the 2 equations and solve for y

substituting into (1)

y = 4(- 3) + 7 = - 12 + 7 = - 5

solution is (- 3, - 5 )

Answer:

(- 3, - 5 )

Step-by-step explanation:

It wont always be easy, but always try to do what ' s right!    

In a world of worriers, be the warrior!         

When nothing goes right, go left.